Performance of a New, Rapid Assay for Detection of Trichomonas vaginalis - Kurth, Ann (American Society for Microbiology, 2004)
Trichomonas vaginalis infection is highly prevalent, may have serious health consequence, and is readily treatable. However, screening has been limited by currently available tests, which tend to be insensitive, expensive, or require a delay before results are reported. The XenoStrip-Tv (Xenotope Diagnostics, Inc., San Antonio, Tex.) was evaluated on vaginal swab specimens from 936 women attending sexually transmitted disease clinics in Seattle, Wash. (n = 497), and Birmingham, Ala. (n = 439). T. vaginalis prevalence by culture (InPouch; Biomed) was 8.7% in Seattle and 21.0% in Birmingham. Compared to culture, the XenoStrip assay in Seattle was 76.7% (95% confidence interval [95% CI] = 61.4 to 88.2) sensitive and 99.8% (95% CI = 98.8 to 99.9) specific, and in Birmingham it was 79.4% (95% CI = 69.6 to 87.1) sensitive and 97.1% (95% CI = 94.8 to 98.6) specific. The positive predictive values were 97.1% in Seattle and 87.9% in Birmingham; the negative predictive values were 97.8 and 94.7%, respectively. Rapid test performance did not vary by vaginal symptoms or by the presence of other vaginal or cervical syndromes or infections. The sensitivity did vary by day of culture-positive result, with a 71% decline in XenoStrip sensitivity for every additional day delay until T. vaginalis was first detected in cultures (odds ratio = 0.29, 95% CI = 0.18 to 0.49). The rapid assay was more sensitive than wet preparation microscopy (78.5% versus 72.4% [P = 0.04]) but was less specific (98.6% versus 100% [P = 0.001]). The XenoStrip rapid assay is well suited for use in settings with a moderately high prevalence of T. vaginalis infection, particularly when microscopy is not practical.